2013
DOI: 10.5194/isprsarchives-xl-5-w1-1-2013
|View full text |Cite
|
Sign up to set email alerts
|

Robust extraction of image correspondences exploiting the image scene geometry and approximate camera orientation

Abstract: ABSTRACT:Image-based modeling techniques are an important tool for producing 3D models in a practical and cost effective manner. Accurate image-based models can be created as long as one can retrieve precise image calibration and orientation information which is nowadays performed automatically in computer vision and photogrammetry. The first step for orientation is to have sufficient correspondences across the captured images. Keypoint descriptors like SIFT or SURF are a successful approach for finding these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
(15 reference statements)
0
11
0
2
Order By: Relevance
“…how undetectable and unmodelled systematic errors affects the accuracy of final results. Camera network with high redundancy and intersection angles close to 90 degrees are more reliable if compared to image sequences as usually seen in SfM procedures (Alsadik et al, 2013). In this paper some qualitative and quantitative analyses using different UAV and terrestrial camera network configurations are reported in the case of the digital documentation of a complex archaeological structure -the roman theatre in Ventimiglia, Italy.…”
Section: Introductionmentioning
confidence: 99%
“…how undetectable and unmodelled systematic errors affects the accuracy of final results. Camera network with high redundancy and intersection angles close to 90 degrees are more reliable if compared to image sequences as usually seen in SfM procedures (Alsadik et al, 2013). In this paper some qualitative and quantitative analyses using different UAV and terrestrial camera network configurations are reported in the case of the digital documentation of a complex archaeological structure -the roman theatre in Ventimiglia, Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Using this computer vision technique the geometric structure of the 3D scene and the pose of the camera at each image can be quickly recovered from a series of overlapping, offset images. (Alsadik et al, 2013;Guidi et al, 2010;Guidi & Remondino 2012;Koska & Kremen, 2013;Lerma et al, 2010;Rodriquez 2012;Wenzel et al, 2013). This new approach to softcopy photogrammetry generates very dense 3D colour point clouds quite similar in size to the one produced from laser scanning surveys.…”
Section: Geometry Surveymentioning
confidence: 99%
“…The new approach to softcopy photogrammetry realized by Structure from Motion (SfM) and MVS (Multi-View Stereo) algorithms generates very dense 3D color point clouds quite similar in size to those produced from laser scanning surveys [18][19][20][21][22][23]. However, even if software evolution in this field is very fast and performance is good in terms of processing time, and the amount of manageable data and obtainable precisions are gradually improving, these procedures may not always be considered reliable.…”
Section: Geometry Surveymentioning
confidence: 99%